The Impact of Firm Size Moderates the Influence of Capital Structure, Operating Capacity, Liquidity - Davy Parsaoran Hinsa; Indriana Titerlie; Mark Fritz Imanuel (Journal of Economics and Business UBS, 2026)
Financial distress has become a critical global concern affecting firms across industries, particularly in the post-pandemic economic recovery period characterized by supply chain disruptions, volatile exchange rates, inflationary pressures, and shifting consumer behaviors. In Indonesia, the transportation and logistics sector has experienced significant financial challenges during 2022–2024, with several listed companies reporting consecutive losses and deteriorating liquidity positions, raising urgent questions about the determinants of financial distress and the protective or amplifying role of firm-specific characteristics. This study aims to analyze the impact of firm size moderating the influence of capital structure, operating capacity, liquidity on financial distress in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. This study uses a quantitative approach with a causal-effect research design, where the sample is determined through purposive sampling and data sources are obtained from annual financial reports and company sustainability reports. Data processing uses Stata with moderated regression analysis. The results indicate that capital structure and operating capacity have an insignificant effect on financial distress, while liquidity has a negative and significant effect on financial distress. Meanwhile, the indirect relationship shows that firm size has no moderating effect on the influence of operating capacity or capital structure on financial distress, while firm size has a moderating or strengthening effect on the influence of liquidity on financial distress.